2018
DOI: 10.7717/peerj.4439
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms and web user experience

Abstract: BackgroundDepression, as one of the most prevalent mental disorders, is expected to become a leading cause of disability. While evidence-based treatments are not always easily accessible, Internet-based information and self-help appears as a promising approach to improve the strained supply situation by avoiding barriers of traditional offline treatment. User experience in the domain of mental problems therefore emerges as an important research topic. The aim of our study is to investigate the impact of depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…Overall, our results align with a recent study investigating the impact of depressive symptoms on web user experience measures, indicating that mood may be a factor influencing technology usability [74]. Additionally, recent research investigating the relationship between user perceptions and user characteristics has shown that older adults demonstrate positive attitudes toward mobile technologies and report technologies' complexity.…”
Section: Principal Findingssupporting
confidence: 90%
“…Overall, our results align with a recent study investigating the impact of depressive symptoms on web user experience measures, indicating that mood may be a factor influencing technology usability [74]. Additionally, recent research investigating the relationship between user perceptions and user characteristics has shown that older adults demonstrate positive attitudes toward mobile technologies and report technologies' complexity.…”
Section: Principal Findingssupporting
confidence: 90%
“…Especially the latter result reflects the role of users' expectations regarding an e-mental health app, as users with good computer skills might expect potential features with a higher level of technological sophistication than available in the app. Taking the fact into consideration that depressed patients in former studies seem to be less able to concentrate on complex website presentations 31 and to show an impaired perception of content, 30 our results highlight the suitability of the app for the specific target group. In our sample, patients showed less computer skills than the healthy controls which explain the negative association of depression scores and the respective level of acceptance towards the app.…”
Section: Discussionsupporting
confidence: 56%
“…However, a higher depressive mood, as evaluated by the GDS, was negatively associated with the satisfaction perceived by participants using the device. Similarly, a recent study investigating the impact of depressive symptoms on measures of web user experience found a significant association between depressive symptoms and subjective user experience [ 63 ]. These results indicate that mood may be a factor influencing technology usability and may warrant further guidance and/or targeted approaches in the use of these technologies by specific populations.…”
Section: Discussionmentioning
confidence: 92%